FIQH PERSPECTIVES ON DIGITAL ZAKAT: MAPPING GLOBAL SCHOLARSHIP THROUGH BIBLIOMETRIC ANALYSIS - Muhamad Dupi; Inayat Ullah Baloch (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2025)
In this research paper, fiqh views on digital zakat are examined based on an analysis of 188 articles published in the years 2017-2025 and indexed in Scopus. It is based on VOSviewer as the main instrument since it tends to map the research tendencies, collaboration patterns, and thematic groups in order to present the overall picture of the global discussion. The findings indicate that the level of scholarly interest has been growing significantly, and the focus on the topic is expected to reach its highest point by 2021-2024 and show the rise of the topicality of the integration of Islamic jurisprudence and digital financial practices. Malaysia and Indonesia are the future contenders that will help them with well established Islamic finance ecosystems and institutional partnerships. It analyses five primary clusters; the intersection of Islamic finance and global issues, trust and technology adoption, geographical and socio-economic contexts, managing zakat with blockchain, and digitalizing the Islamic finance. As digital zakat has the advantage of efficiency, transparency, and compatibility with the Sustainable Development Goals (SDGs), the same has issues with digital literacy, infrastructure, and duality of the zakat institutions towards society and God.